Period planning and budgetary control - Evans, Edward C. D. (London : Macdonald & Co. (publishers) Ltd, 1964)
This short work has been written as an aid to the understanding of one of the pillars of management accounting. It will be of some value to all those interested in business management.
Volume 1
Includes bibliographical footnotes.
hza 29/08/2018
Loans
Keywords: Management accounting; Business management